Does A Group Supervised Shoulder Impingement Class Improve Shoulder Pain, Disability and Generic Health Outcomes? A Summative Service Evaluation - Darren Abramson (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2018)
Background: Patients with shoulder impingement syndrome (SIS) suffer pain and disability and present enormous health and fi nancial challenges to the NHS. There is limited evidence for many of the commonly used physiotherapy treatment interventions. Research suggests deprivation, age, gender and attendance are possible predictors of poor treatment outcome in common MSK conditions. The present author set up and ran a physiotherapy led group based SIS class to improve generic health outcomes and reduce shoulder pain and disability. Method: 236 SIS patients were referred over a 22 month period. 154 completed the once weekly six week course. 82 failed to complete the class. Generic health outcomes were measured with the Euroqol EQ-5D-5L with condition specifi c outcome measured using the Shoulder Pain and Disability Index (SPADI). Covariates possibly predictive of poor treatment outcome were analysed using linear regression and included Townsend Deprivation Score (TDS), age and gender. Class completers and non-completers were compared to determine any association with TDS, age and gender. Results: Statistically signifi cant improvements in generic health (t -7.77, df 153, p < 0.001) and shoulder pain and disability (t -9.36, df 153, p < 0.001) were found post intervention. No association for the predictive utility of TDS, age and gender on EQ-5D-5L and SPADI outcome was found. Statistically signifi cant differences between class completers and non-completers for TDS t (181.17)=-3.62, p < 0.001) and age (t (134.72)=2.41, p = 0.017) were found. Younger patients and those from more deprived areas attended fewer classes. No association was found between gender and non- attendance. TDS, age and gender have no association with class non-completion type be it never attended or attended then did not attend (DNA). Conclusion: Physiotherapists play a key role in managing the third most common MSK pathology. This evaluation suggests positive outcomes for those completing a group based SIS class on both health and shoulder pain and disability. SIS patients meeting inclusion criteria should be routinely fed into group based classes.